Alliance between Corporations and Non-profit Organisations for CSR practices. An explorative Study in Malaysia Context - Bamigboye, Akintomide (2008)
This is an explorative study of alliances between non-profit organisation and corporations in Malaysia. The research employed case study analysis to examine the relationship between the two parties. Emerging issues during the explorative study of variables in alliance development process and secondary sources of data most significantly, parties’ published reports on the partnership formed the basis of opinion. The study found overwhelming evidence that the Malaysian NPOs are on the verge of a paradigm shift that could lead to new ways of interacting; making partnership with corporate organisation a more desirable way of solving humanitarian, environmental, and community developmental issues rather than adversarial approach. The study among other things confirmed that the type of alliance formed in Malaysia are based on contractual agreements; they are also proactive alliances grounded in economics theories (resource- based theory), however alliance objectives are found to be focusing on the external environment of the corporations and the level of interaction are more of arms-length and interactive relationship with negligible traces of intensive alliance. Conclusion and recommendations on further actions are offered at the end of the paper.